Difference in Postural Control during Quiet Standing between Young Children and Adults: Assessment with Center of Mass Acceleration. - Naoko Oba; Shun Sasagawa; Akio Yamamoto; Kimitaka Nakazawa (PLoS ONE)
The development of upright postural control has often been investigated using time series of center of foot pressure (COP), which is proportional to the ankle joint torque (i.e., the motor output of a single joint). However, the center of body mass acceleration (COMacc), which can reflect joint motions throughout the body as well as multi-joint coordination, is useful for the assessment of the postural control strategy at the whole-body level. The purpose of the present study was to investigate children's postural control during quiet standing by using the COMacc. Ten healthy children and 15 healthy young adults were instructed to stand upright quietly on a force platform with their eyes open or closed. The COMacc as well as the COP in the anterior-posterior direction was obtained from ground reaction force measurement. We found that both the COMacc and COP could clearly distinguish the difference between age groups and visual conditions. We also found that the sway frequency of COMacc in children was higher than that in adults, for which differences in biomechanical and/or neural factors between age groups may be responsible. Our results imply that the COMacc can be an alternative force platform measure for assessing developmental changes in upright postural control.